Mengembangkan Kemampuan Berpikir Kritis Warga Negara Muda Melalui Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan - Nuraeni, Wulan; Komalasari, Kokom; Mahpudz, Asep (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Civic education have an important position to prepare young people for their roles and responsibilities as good citizens. Civic education needs to be humanist, dialogical, critical, and put forward character building to build the critical thinking ability of students in the life of democratic society. Based on these reviews, this article aims to describe develop critical thinking skills of young citizens through learning civic education to realize students who have the ability to think critically. The article is writen by descriptive qualitative research method with literature study approach. The source of data is come from the books, journals, and other scientific articles which collected by documentation techniques and discourse identification. While the data analysis techniques using content analysis techniques. The result of this discussion shows that Civics based on critical theory can be constructed through 3 rationality models namely technical rationality, hermeunetic rationality and emancipatory rationality that emphasizes the dialogical method and the role of teachers as transformative educators. So the students can be educational subjects with autonomy, freedom and critical thinking skills to become critical and transformative citizens.